2016
DOI: 10.1016/j.aquatox.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and immunotoxicity induced by graphene oxide in zebrafish

Abstract: a b s t r a c tGraphene oxide (GO) has been extensively explored as a promising nanomaterial for applications in biology because of its unique properties. Therefore, systematic investigation of GO toxicity is essential to determine its fate in the environment and potential adverse effects. In this study, acute toxicity, oxidative stress and immunotoxicity of GO were investigated in zebrafish. No obvious acute toxicity was observed when zebrafish were exposed to 1, 5, 10 or 50 mg/L GO for 14 days. However, a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(103 citation statements)
references
References 54 publications
(55 reference statements)
13
89
1
Order By: Relevance
“…26 For instance, Chen et al reported that exposure to graphene oxide led to the cellular alterations, such as vacuolation, histolysis and disintegration of cell boundaries, in the liver and intestine of zebrash. 27 In consistent with the ndings reported by Chen et al, 27 we also found that exposures to high concentrations of CS-MoS 2 micro-sheets (10 mg L À1 and 20 mg L…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…26 For instance, Chen et al reported that exposure to graphene oxide led to the cellular alterations, such as vacuolation, histolysis and disintegration of cell boundaries, in the liver and intestine of zebrash. 27 In consistent with the ndings reported by Chen et al, 27 we also found that exposures to high concentrations of CS-MoS 2 micro-sheets (10 mg L À1 and 20 mg L…”
Section: Discussionsupporting
confidence: 81%
“…37 Consistent with the ndings reported by Chen et al, 27 we further found that the expressions of these three cytokines were remarkably increased aer exposure to a high concentration of CS-MoS 2 micro-sheets (20 mg L À1 ), which indicated that high concentration of CSMoS 2 micro-sheets caused strong proinammatory response in gill and liver (Fig. 5).…”
Section: -29supporting
confidence: 81%
“…ROS act as second messengers in many intracellular signalling cascades and lead to cellular macromolecular damage, such as membrane lipid breakdown, DNA fragmentation, protein denaturation and mitochondrial dysfunction, which greatly influence cell metabolism and signalling [175177]. The interactions of GO with cells can lead to excessive ROS generation, which is the first step in the mechanisms of carcinogenesis, ageing, and mutagenesis [83, 122].…”
Section: Possible Toxicity Mechanisms Of Gfnsmentioning
confidence: 99%
“…The interactions of GO with cells can lead to excessive ROS generation, which is the first step in the mechanisms of carcinogenesis, ageing, and mutagenesis [83, 122]. Oxidative stress had a significant role in GO-induced acute lung injury [30], and the inflammatory responses caused by oxidative stress often emerged upon exposure to GFNs [133, 177, 178]. The activity of SOD and GSH-PX decreased after exposed to GO in a time- and dosage-dependent manner [82, 106, 119].…”
Section: Possible Toxicity Mechanisms Of Gfnsmentioning
confidence: 99%
“…Two month old zebrafish were exposed to 1, 5, 10, and 50 mg/L GO for 14 days with a 50% static renewal of the medium every day (Chen et al 2016). No obvious acute toxicity was observed; however, histological analysis indicated that in liver and intestine, cellular vacuolation, loose arrangement, histolysis, and disintegration of cellular boundaries occurred (Chen et al 2016).…”
Section: Toxic Effects Of Gpnmentioning
confidence: 99%